Мокиенко В. М., Никитина Т. Г., Николаева О. К. Большой словарь русских пословиц - Тищенко, О. (Мовознавство, 2011)
Рецензія на книгу: Мокиенко В. М., Никитина Т. Г., Николаева О. К. Большой словарь русских пословиц. М .: ЗАО «Олма Медиа Груп», 2010.— 1024 с.